2008
DOI: 10.1093/hmg/ddn072
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association scans identified CTNNBL1 as a novel gene for obesity

Abstract: Obesity is a major public health problem with strong genetic determination; however, the genetic factors underlying obesity are largely unknown. In this study, we performed a genome-wide association scan for obesity by examining approximately 500 000 single-nucleotide polymorphisms (SNPs) in a sample of 1000 unrelated US Caucasians. We identified a novel gene, CTNNBL1, which has multiple SNPs associated with body mass index (BMI) and fat mass. The most significant SNP, rs6013029, achieved experiment-wise P-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
124
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 52 publications
10
124
1
2
Order By: Relevance
“…7 online). In addition to these, the KARE GWA data provided corroboration of BMI signals previously reported in the vicinity of the MC4R (in our data, rs17782313, P ¼ 1.9 Â 10 À4 ) and CTNNBL1 (rs6067731, P ¼ 0.02) genes 8,9 (Supplementary Table 8 online).…”
Section: Body Mass Indexsupporting
confidence: 90%
“…7 online). In addition to these, the KARE GWA data provided corroboration of BMI signals previously reported in the vicinity of the MC4R (in our data, rs17782313, P ¼ 1.9 Â 10 À4 ) and CTNNBL1 (rs6067731, P ¼ 0.02) genes 8,9 (Supplementary Table 8 online).…”
Section: Body Mass Indexsupporting
confidence: 90%
“…Obesity is a major public health problem that is strongly influenced by genetic factors that remain largely unknown [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Twin studies have generally found heritability estimates of 0.75 to 0.85 for BMI and approximately 0.70 for weight [2]. Genome-wide association (GWA) studies have provided evidence that several loci are associated with common obesity mostly in populations of European descent [3][4][5][6][7][8][9][10][11][12][13][14][15]. The first such loci reported was the fat-mass and obesity-associated gene (FTO) [3,16,17].…”
Section: Introductionmentioning
confidence: 99%